An assessor-blinded, randomized comparison of efficacy and tolerability of switching from olanzapine to ziprasidone and the combination of both in schizophrenia spectrum disorders. (February 2017) - Wang, Huai-Hai; Cai, Min; Wang, Hua-Ning; Chen, Yun-Chun; Zhang, Rui-Guo; Wang, Ying; McAlonan, Grainne M.; Bai, Yuan-Han; Wu, Wen-Jun; Guo, Li; Zhang, Ya-Hong; Tan, Qing-Rong; et al.
Abstract: Background: Ziprasidone (ZIP) is often used with olanzapine (OLZ) in 'switch' and combination therapy but empirical evidence to support these strategies is limited. Objective: This study was therefore designed to compare the efficacy and tolerability of switching from OLZ to ZIP, the combination of both medications, and OLZ and ZIP monotherapy, in patients with schizophrenia spectrum disorders (SSD). Methods: In this 12 week open-label, assessor-blinded randomized trial, 148 patients with SSD who had not used antipsychotics for at least 3 months were assigned to ZIP (n = 49) or OLZ monotherapy (n = 31); OLZ for 4 weeks then a switch to ZIP (OLZ/ZIP, n = 35); or combination therapy (OLZ + ZIP, n = 33). The severity of psychosis and abnormal involuntary movements was evaluated at baseline, 1, 2, 4, 8, and 12 weeks using standard instruments. Baseline-to-endpoint changes in weight gain and metabolic measures were compared. Results: The efficacy of both OLZ/ZIP and OLZ + ZIP was comparable OLZ monotherapy and better than ZIP monotherapy in reducing overall psychotic and negative symptoms at most 8 and 12 week measurement points. Changes in weight gain, glucose, and lipid measures did not differ between OLZ/ZIP and OLZ + ZIP, but were markedly higher following OLZ monotherapy. The OLZ + ZIP group had the lowest overall incidence of adverse events and extrapyramidal symptoms of all the treatment regimens. Conclusions: We conclude that combining ZIP and OLZ at the outset of treatment is superior to switching from OLZ to ZIP in terms of improving psychotic symptoms and limiting movement side effects without increasing the risk of metabolic syndrome.